Early Intervention With Cecal Fermentation Broth Regulates the Colonization and Development of Gut Microbiota in Broiler Chickens - Gong, Yujie; Yang, Hua; Wang, Xin; Xia, Wenrui; Lv, Wentao; Xiao, Yingping; Zou, Xiaoting (Frontiers in Microbiology, 2019)
The aim of this study was to investigate the effect of the fermentation broth from broiler cecal contents on the colonization and development of the gut microbiota in newly hatched broiler chicks. The fermentation broth was made by a chemostat system using the cecal contents form a donor chicken as the source of inoculum. A total of 120 newly hatched broiler chicks were randomly divided into two groups. One group (F group) was orally inoculated with the fermentation broth, and the other (C group) was treated with an equal amount of PBS solution. 16S rRNA gene sequencing was used to investigate the differences in the cecal microbiota of the broiler chickens between the two groups on days 1, 3, 7, 14 and 28. Moreover, the concentrations of short-chain fatty acids (SCFAs) in the cecal contents were analyzed by gas chromatography. The results showed that the abundances of genera Escherichia-Shigella and Enterococcus decreased sharply in the F group on days 1 and 3 by the early intervention with cecal fermentation broth. In contrast, the relative abundance of the genus Bacteroides on days 1, 3 and 7, and the family Ruminococcaceae on days 1, 3 and 28 were enhanced in the F group, respectively. In terms of SCFAs, the concentrations of acetate on day 28, propionic acid on days 1, 3, 7, 14 and 28, butyrate on day 1, and isovalerate on day 14 were significantly higher in the F group when compare with the C group. Overall, these results suggested that early intervention with cecal fermentation broth might have beneficial effects on broilers gut health, which might be attributed to the alterations in the gut microbial composition and the increased concentrations of SCFAs.